2004
DOI: 10.1002/jms.657
|View full text |Cite
|
Sign up to set email alerts
|

Matrix‐dependent cationization in MALDI mass spectrometry

Abstract: The matrix dependence in cationization processes, the competition between cationization and protonation and the question of whether gas-phase cation transfer or attachment of free cations dominates in matrix-assisted laser desorption/ionization mass spectrometry were studied. Two different sample preparation methods were employed, the dried-droplet sample preparation and a mixture of solid matrix, analyte and salt. The latter ensures that the formation of cation adducts takes place in the gas phase. By monitor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
35
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(38 citation statements)
references
References 56 publications
2
35
0
Order By: Relevance
“…We propose that, for porphyrins, the cationized matrix might well be the cation donator to the analytes, whereas analyte cationization with other matrices seems to occur predominantly through attachment of free cations in the gas phase (Zhang & Zenobi, 2004). Ab initio calculations showed that Li þ is attached to the porphyrin cavity and not to the F atoms of the C 6 F 5 groups.…”
Section: A Protonation Versus Cationizationmentioning
confidence: 98%
“…We propose that, for porphyrins, the cationized matrix might well be the cation donator to the analytes, whereas analyte cationization with other matrices seems to occur predominantly through attachment of free cations in the gas phase (Zhang & Zenobi, 2004). Ab initio calculations showed that Li þ is attached to the porphyrin cavity and not to the F atoms of the C 6 F 5 groups.…”
Section: A Protonation Versus Cationizationmentioning
confidence: 98%
“…Cationization by alkali metal cations such as Na + and K + is one of the secondary ionization processes that occur in MALDI [25][26][27][28][29][30][31][32][33]. Cationization is also believed to influence protonation, deprotonation, and electron transfer ionization processes that occur in MALDI.…”
Section: Introductionmentioning
confidence: 99%
“…4(a), but without PA present in the spectrum. The most intense peaks result from alkalimetal sodium ions Na + and kalium K + , Salt impurities that may originate from the matrix, the analyte, solvents, glassware and from the surface of the sample carrier [14] . The results suggested that uncoated coumarin particles cannot be directly ionized under this experimental condition.…”
Section: Resultsmentioning
confidence: 99%